Comparing the effects of hopping and strength-balance exercises on the selected muscles strength and balance in male athletes with chronic ankle instability - Fatemeh Hosseinzadeh; Ali asghar Norasteh (Shahid Beheshti University of Medical Sciences, 2022)
Background and Aims: The present study aims to compare the effects of two types of hopping and strength-balance exercises on the balance and strength of selected muscles in athletes with chronic ankle instability.Methods: Participants were 30 male athletes with chronic ankle instability, who were selected using a purposive sampling method and randomly divided into two groups of hopping and strength-balance exercise. A questionnaire was used to record demographic characteristics and the information about the history of sports. To measure strength, a dynamometer was used. The Standing stork test and Y balance test were used to measure static and dynamic balances, respectively. Analysis of covariance and the Least Significant Difference post hoc test were used to compare the means.Results: There was a significant difference in the static balance (P<0.001) and the total dynamic balance between the two groups (P<0.001). The strength-balance exercise group in all directions of the Y balance test performed better than the hopping exercise group. Moreover, hip abduction strength (P=0.02) and the inversion (P=0.005) and eversion strengths (P=0.002) of ankle were significantly different between the two groups after training, where the strength-balance group had higher scores. There was no significant difference between the two groups in other factors.Conclusion: Both hopping and strength-balance exercises can be effective in improving the balance and strength of male athletes with chronic ankle instability, where the strength -balance exercise program seems to be more useful due to its comprehensiveness and given that it emphasizes the improvement of balance, proprioception, trunk strength, and lower limb strength, and can have a greater effect on the fast recovery of athletes.